2011
DOI: 10.1002/iroh.201111311
|View full text |Cite
|
Sign up to set email alerts
|

The Golden Gate Leech Helobdella californica (Hirudinea: Glossiphoniidae): Occurrence and DNA‐Based Taxonomy of a Species Restricted to San Francisco

Abstract: Leeches of the genus Helobdella are small brooding annelids that inhabit lakes and streams on every continent, notably in South America. The type species, H. stagnalis L. 1758, occurs in Europe and North America. Here I provide novel observations on the occurrence, morphology, and parental care patterns of the related H. californica, a taxon described in 1988, based on specimens collected in Stow Lake, Golden Gate Park, San Francisco. In 2007, the original H. californica population no longer existed, possibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…H. triserialis USA, Siddall & Borda 2003;Klemm et al 2012) and H. californica (Kutschera 1988(Kutschera , 1989(Kutschera , 2011, living freshwater snails appear to be the preferred host organism of H. austinensis n. sp. Our prey selection studies revealed that H. austinensis n. sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…H. triserialis USA, Siddall & Borda 2003;Klemm et al 2012) and H. californica (Kutschera 1988(Kutschera , 1989(Kutschera , 2011, living freshwater snails appear to be the preferred host organism of H. austinensis n. sp. Our prey selection studies revealed that H. austinensis n. sp.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is conceivable that the species discovered in Austin, Texas, is an imported leech from South America. Circumstantial evidence suggests that the taxa H. europaea and H. californica, which are distributed in aquatic freshwater ecosystems of Europe, Australia, New Zealand, South Africa, Hawaii, Thailand, and California, respectively, are likewise imported species from South America (Kutschera 2004(Kutschera , 2011. On the other hand, phylogenetic analyses document that H. austinensis (i.e., "H. robusta TX AU1") resides in a monophyletic clade of North American Helobdella species (Oceguera-Figueroa et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on CO-I-sequences acquired in our laboratory for H. verbana and other leech species (Kutschera 2010(Kutschera , 2011Kutschera et al 2007Kutschera et al , 2013, supplemented by additional GenBank CO-I-data, the results shown in Table 1 were obtained. The type species H. medicinalis and its sister taxon H. verbana differ by ca.…”
Section: Phylogenetic Analysis Divergence Time and Geographic Distrimentioning
confidence: 99%
“…While the first taxon, the type species of the class Hirudinea Lamarck, 1818 (sangsue médicinale, i.e., the medicinal leech), is still accepted today as a valid species, Lamarck's "H. sanguisorba" remains an enigma. and Kutschera 2011;Elliott and Dobson 2014). Utevsky and Trontelj (2005) provided a key to all known European species in the genus Hirudo, and Kutschera (2012aKutschera ( , 2012 summarized their geographical distribution.…”
Section: Introductionmentioning
confidence: 99%